(untitled) (One Health & Risk Management, 2022)
Introduction Ε-health (eH) is a basic component of current health care provision. The cornerstone of eH is the electronic health record (EHR) system. Material and methods The purpose of this survey is to assess the Greek EHR application by Greek family doctors, taking into consideration the brief period of EHR implementation in Greece. We adapted a preexisting questionnaire, with permission, translating and standardizing it in Greek. The questionnaire focused on computer use capability, EHR usage, and efficiency in daily clinical practice, user satisfaction and global user evaluation of the application. 175 family doctors filled out the questionnaire in February 2019. Results Low usage rates, minimal facilitation in daily practice, competency issues, and moderate user satisfaction were among our findings. Conclusions Greek EHR has several problems and inadequacy areas. Reversing these problems and optimizing the application, then reevaluating the results after a wider period of implementation is important.